The law of the strongest? Exploring the drivers of firm performance during the COVID-19 crisis - Franco, Guido (OECD Publishing, 2023)
Using data on more than 150.000 non-financial companies operating in both manufacturing and services sectors around the world, we analyse the drivers of firm performance throughout the whole COVID cycle (until end 2021). We highlight three key results. First, if anything, larger and older firms did worse than smaller and younger ones in terms of revenues and investment spending, both during COVID-19 and the subsequent recovery. Even in sectors that were under scrutiny from a competition standpoint, such as technology and healthcare, larger firms did not systematically over-perform. Second, ex-ante financial strength attenuated the effects of the shock on revenues during the COVID cycle. Third, there is some evidence of debt overhang: firms that entered the crisis with a higher leverage ratio invested less than others, including on R&D, both in 2020 and in 2021, while firms that became more debt-burdened during the pandemic tended to record weaker investment spending during the recovery. These insights shed light on market power, competition, and more generally on the performance of the corporate sector since the start of COVID-19 pandemic
Keywords: Economics